Seed metering device evaluation by Grease Belt Method - KUMAR, DEVESH; TRIPATHI, ASHOK; PRAKASH, OM; JOSHI, PRATIBHA; KHAN, KALAY; KUMAR, MANISH (The Indian Journal of Agricultural Sciences, 2021)
Soybean [Glycine max. (L.) Merr.] serve as one of the most valuable crop in the world; not only for oil purpose italso feed for livestock and aquaculture. A simple laboratory grease belt method for soybean planter was developed fortesting and calibrating the seed metering mechanism. The study was conducted in the year 2017, in the Departmentof Farm Machinery and Power Engineering, Allahabad. The main frame consists of variable speed drive, and greasecoated belt that are fitted with necessary provisions. The second frame consists of seed hopper and seed metering unit.The field and laboratory methods have been developed and used for evaluation of planter performance, each methodhaving its own advantages and shortcomings. In the present study, grease belt was used for laboratory evaluation ofwheel type seed-metering device and investigated the feeding quality, missing index, seed rate, and uniformity ofseeds in the row at various speed of grease belt. The results from grease belt methods were in good agreement andanalysis of variances showed that seed-metering device with 18 cells in 50 rpm performed better than seed-meteringdevice with 32 cells and in other speeds. Calibration of the manually operated seed-cum-fertilizer soybean planterhas been done in the laboratory. During calibration of planter, it found that there was less missing of soybean due tocircular shape of seed. Due to full hopper the pressure was high at the bottom and due to this force on seed of soybeaneasily reaches at the metering device.